The Study of Temperature Distribution on A Cylinder of Suzuki 250gsx Engine Fueled with Gasoline Blends Using Finite Element Analysis - Lutfi Y. Zeidan; Mohammed KH. Abbass; Ali Z. Asker (Diyala Journal of Engineering Sciences, 2014)
The alcohol–gasoline blend fuels nowadays are increasingly used instead  of gasoline in automobiles. In the present study, the temperature distribution within the cylinder of Suzuki 250Gsx motor was studied, taking in account the use of gasoline, E10- gasoline and E20-gasoline blends as a fuel, separately. The temperature fields are calculated  using ANSYS 11 software. The geometric model and dimensions of the cylinder was established using Solid work 2003 program then imported by ANSYS11. After applying the boundary conditions and taking the assumptions in account, the results illustrated that the  interchange of gasoline by E10-gasoline and or E20-gasoline blends has a variety of thermal  load on the cylinder. Where the temperature distributed decreasingly towards the axial and radial directions. In addition, the engine becomes colder as the ethanol percentage in the fuel been 20%. This may provide supporting information for new designs for using E10-gasoline  and or E20-gasoline blends on SI engines so that not to effect the engine operation and  lubricating oil performance